Pengaruh Intellectual Capital Terhadap Profitabilitas, Produktivitas, Dan Penilaian Pasar Pada Perusahaan Yang Konsisten Terdaftar Di LQ45 BEI Tahun 2010-2012 - Saleh, Faisal; Muthmainnah, Muthmainnah (Future : Jurnal Manajemen dan Akuntansi, 2016)
This paper examines the association between Intellectual Capital (IC) and corporate performance, can be explained by profitability, productivity, and market valuation of companies listed on Bursa Efek Indonesia by investigating value creation efficiency , as measured by Value Added Intellectual Capital ( VAIC). The independent variabel that used in this research are intellectual capital that proxy by Value Added Intellectual Capital ( VAIC), physical capital that proxy by Value Added Capital Employed (CEE), human capital that proxy by Value Added human capital ( HCE) and structural capital that proxy by Value Added Structural capital(SCE). The dependent variabel that used in this research are profitability that proxy by return on asset (ROA), productivity thar proxy asset turn over ( ATO) and market valuation that proxy market capitalization( MB)Â  The research used secondary data from Indonesia Capital Market Directory (ICMD) that given to 91 companies in the LQ45 Bursa Efek Indonesia years 2010 -2012.Â  Correlation and regression models were used to examine the relationship between corporate value creation efficiency and firmsâ profitability, productivity and market valuation. The findings from this study show that intellectual capital ( VAIC) influenced profitability and productivity significantly but didnât influence market valuation. The study also suggests that individually , each component of the VAIC commands different values compared to the aggregate measure , which implies that the investors place different value on the three VAIC components.Â  The result also indicates that physical capital efficiency is not significant variable related profitability, productivity and market valuation. Human capital efficiency is of great importance in enhancing the productivity of the companies. Structural capital efficiency is significant variable related profitability and productivity, but fails to explain market valuation.Â  Â Kata Kunci : Intellectual capital, Profitability, Productivity, Market valuation